Political Federalism and minorities In Nigeria - EMINA, Kemi Anthony (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
This study explores how the federal model in Nigeria has promoted pluralism in accordance with the current constitution, acknowledging diversity and cultivating a sense of loyalty and belonging among all citizens of the Federation. The analysis commences by tracing the historical development of Nigeria’s federal system. Subsequently, it examines the practical implementation of federalism in contemporary Nigeria. The study delves into the ethnic minorities in Nigeria and the politicisation of ethnicity. Furthermore, it elucidates the constitutional provisions pertaining to political rights, representation, and participation, including the incorporation of Sharia Law into Nigeria’s federal system. Finally, the study concludes by examining the political participation of minorities at various administrative levels, encompassing the village, state, and national levels.